Everolimus compliance and persistence among tuberous sclerosis complex patients with renal angiomyolipoma or subependymal giant cell astrocytoma. (3rd June 2019) - Song, Xue; Said, Qayyim; Tran, Oth; Krueger, Darcy A.; Bissler, John
Abstract: Objective: Everolimus is the only FDA approved drug to treat renal angiomyolipoma or subependymal giant-cell astrocytoma (SEGA) in tuberous sclerosis complex (TSC). Potential differences exist between patients with commercial and Medicaid insurance on everolimus use; however, there is limited information from the real world. This study compared compliance and persistence of everolimus between commercial and Medicaid patients using US claims data. Methods: Patients with ≥1 claim of TSC with renal angiomyolipoma or SEGA were selected from the MarketScan commercial (1 January 2009–31 August 2016) and Medicaid (1 January 2009–30 June 2015) databases. Patients were followed from index date (the earliest date of TSC, renal angiomyolipoma or SEGA diagnosis) to death or end of data. Non-persistence, defined as ≥60 day gap without everolimus, and medication possession ratio (MPR) were assessed among the subset of patients with ≥1 year of follow-up from the first everolimus claim. Results: A total of 1497 TSC patients met the study criteria (896 renal angiomyolipoma only, 411 SEGA only and 190 both). Compared to Medicaid patients ( N  = 513), commercial patients ( N  = 984) had the same ages (22 years) but a shorter length of follow-up (38 vs. 48 months, p  < .001). Medicaid and commercial patients had similar rates of being treated with everolimus (14.4% vs. 13.6%, p  = .668), but it took Medicaid patients a longer time to start everolimus (871 vs. 704 days, p  < .001). Although the non-persistence rate was not significantly different between commercial and Medicaid patients (42.5% vs. 35.1%, p  = .561), the number of days from everolimus initiation to non-persistence was significantly lower for commercial patients (945 vs. 1132, p  < .001). During the 1 year post everolimus initiation, commercial patients had a significantly higher MPR (0.81 vs. 0.74, p  < .001) and higher percentage of patients with MPR ≥0.80 (67.8% vs. 58.1%, p  < .001). Conclusions: Among TSC patients with renal angiomyolipoma or SEGA and treated with everolimus, everolimus MPR was between 0.74 and 0.81. Medicaid patients had lower MPR than commercial patients but better persistence.